Hubungan Literasi Pancasila Dalam Pendidikan Indonesia Yang Berkarakter - Saragih, Desi Karolina (Yayasan Darussalam Bengkulu, 2021)
The purpose of this research is to apply literacy values in Pancasila in character education so that the Pancasila value becomes a guideline. To study Pancasila literacy through the character education discussion methodology. As knowledge in studying Pancasila literacy through the methodology of character education discussion results. Research methodology is a process or classify scientific data that will be used for research purposes. Methodology is also a theoretical analysis of a method or method. The method used in this research is descriptive method which aims to describe, describe and explain events related to Pancasila literacy in character education. In this method, it is described that what is meant in this study is the data collected in the form of words, phrases, paragraphs. And, the results of this study were analyzed which were described or presented. This work can provide new information and enthusiasm for all of us, especially in the field of reading. Pancasila, the culture of Pancasila, this effort can be done through Pancasila Education by teaching Pancasila to the next generation, supported by experience or the learning process. Education is a conscious and planned effort to create an atmosphere of learning and the learning process so that students can actively develop their potential and become good characters. Therefore, the community must practice Pancasila, one of which is the Pancasila literacy movement in schools and colleges